2016
DOI: 10.1073/pnas.1605399113
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional localization of T-cell receptors in relation to microvilli using a combination of superresolution microscopies

Abstract: Leukocyte microvilli are flexible projections enriched with adhesion molecules. The role of these cellular projections in the ability of T cells to probe antigen-presenting cells has been elusive. In this study, we probe the spatial relation of microvilli and T-cell receptors (TCRs), the major molecules responsible for antigen recognition on the T-cell membrane. To this end, an effective and robust methodology for mapping membrane protein distribution in relation to the 3D surface structure of cells is introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
241
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(260 citation statements)
references
References 58 publications
13
241
4
2
Order By: Relevance
“…Scanning angle interference microscopy ( Fig S5B) of T cells encountering lipid bilayers similarly confirmed that there were significant height variations of membrane for cells engaging lipid bilayers (Fig S5C). Notably bright TCR accumulations (microclusters) were closer to lipid bilayers as compared to the entire pool average, which is consistent with recent variable-angle TIRF studies showing TCR pre-enriched at microvillar tips (21). ICAM-1, a bigger molecule, was found farther away from the bilayer (Fig S5B-D).…”
Section: Synaptic Contact Mapping (Scm) Of Tcr-mediated Protrusion-stsupporting
confidence: 90%
“…Scanning angle interference microscopy ( Fig S5B) of T cells encountering lipid bilayers similarly confirmed that there were significant height variations of membrane for cells engaging lipid bilayers (Fig S5C). Notably bright TCR accumulations (microclusters) were closer to lipid bilayers as compared to the entire pool average, which is consistent with recent variable-angle TIRF studies showing TCR pre-enriched at microvillar tips (21). ICAM-1, a bigger molecule, was found farther away from the bilayer (Fig S5B-D).…”
Section: Synaptic Contact Mapping (Scm) Of Tcr-mediated Protrusion-stsupporting
confidence: 90%
“…While not a wide-field detection method, this has been used to track the motion of single nanoparticles, one at a time, by using a xyz translation stage in closed-loop operation, permitting the observation of complex cellular transport processes with a large range and high resolution both spatially and temporally. (142145)…”
Section: Methods For 3d Localizationmentioning
confidence: 99%
“…We found that at both temperatures L-selectin was concentrated on microvilli, 1,2 while CD45 was distributed uniformly throughout the membrane. 1,4,5 Next, we stained T cells with Alexa-647 labelled anti human TCRαβ antibodies at the two temperatures. At 4°C the structure of microvilli on almost all the T cells was intact, and the TCRαβ molecules localized on them (Fig.…”
Section: Supporting Textmentioning
confidence: 99%